Women's Role in Religious Authority Qibla Determination: An Analysis with Neofunctional Theory - Hendrimania, Hendri (Musawa: Journal for Gender Studies, 2025)
This article discusses the involvement of women in religious authority, especially in the practice of determining the Qibla direction. Normatively, Islam does not differentiate between men and women in mastering the science of falak. However, the social role of women is often limited by the construction of patriarchal culture. in this article there are 2 objectives that will be discussed first how the role of women in religious authorities related to the determination of the Qibla in contemporary times and how the study of the theory neofunctionalism on the role of women in religious authorities related to the determination of the Qibla direction in contemporary times, so that the results obtained that the role of women in religious authorities related to determining the direction of the Qibla has a different role where historically the role is held by men based on religious sources (Al-Quran, sunnah, ijma', qiyas) although in contemporary times it can be done by women. As for the point of view of Jeffrey Alexander's Neofunctionalism theory, this study sees that the role of women in determining the Qibla has a dual function, first, the integrative function which is to maintain the continuity of religious tradition with contemporary science; second, the adaptive function, namely opening space for women's participation in the technical realm of religion, third, the symbolic function, namely presenting new legitimacy that religious authority does not exclusively belong to men and the dynamic function, namely correcting gender bias in the practice of religious authority.